P-149 YI IL-33/ST2 Axis Modulates Carcinogenesis in Inflammation-Associated Colorectal Cancer. (March 2016) - Lopetuso, Loris R.; De Salvo, Carlo; Di Martino, Luca; Goodman, Wendy; Scaldaferri, Franco; Gasbarrini, Antonio; Pizarro, Theresa T.
Abstract : Background: It is now well-established that IL-33 and its receptor, ST2, are important factors in the pathogenesis of IBD. Emerging evidence also suggests its critical role in epithelial proliferation and potential contribution to inflammation-driven tumorigenesis that can lead to colorectal cancer (CRC). The aim of our study was to characterize the precise contribution of IL-33/ST2 axis in the azoxymethane (AOM)/dextran sodium sulfate (DSS) model of colitis-associated CRC. Methods: C57/BL6 wild-type (WT), IL-33 KO and ST2 KO mice were given a single dose of AOM (7.4 mg/kg) followed by 2 cycles of 3% DSS for 7 days in drinking water. Body weight, occult blood test, and stool consistency were measured daily to calculate the Disease Activity Index (DAI), and endoscopic and histological evaluation of colons were performed using established scoring systems. Aged-matched WT mice, injected with vehicle and given regular drinking water were used as controls (CT). At 8 weeks post AOM injection mice were sacrificed. IHC, immunofluorescence (IF) and qPCR were done on full-thickness colons for IL-33 and ST2 localization and identification, and mRNA expression, respectively. FACS analysis was performed on resected, isolated polyps in order to functionally characterize ST2+ cells. Results: IL-33, ST2L, and sST2 mRNA transcripts were dramatically elevated in WT versus CT mice. IHC of treated WT mice revealed localization of IL-33 to the colonic epithelium and to cells within the LP morphologically consistent with tissue macrophages. ST2 staining was localized to the intestinal epithelium in tissues immediately adjacent to tumors, while within the tumors themselves, ST2+ cells displayed a spindle/fibroblast-like morphology with a unique distribution throughout the polyps. Little to no staining for both IL-33 and ST2 was present in CT. Using IF, ST2 co-localized with αSMA in polyps; however, ST2 staining was not exclusive for αSMA+ cells. FACS analysis showed a distinct population of CD45 + hematopoietic cells consisting of CD3/CD8 + cytotoxic T cells (CTLs), CD19 + B-lymphocytes, CD11b + CD11c − and CD11b + CD11c + myeloid cells. ST2 was mainly expressed by CTLs, and CD11b + CD11c − and CD11b + CD11c + myeloid cells. Non-hematopoietic cells (CD45−) also expressed ST2. DSS challenge in WT mice resulted in increased body weight loss and DAI versus IL-33 KO and ST2 KO mice. At 5 weeks post AOM injection, experimental mice underwent survival colonoscopy. WT had already developed protruding lesions with abnormal vascular patterns, suggesting pre-tumorous lesions, while IL-33 KO and ST2 KO mice showed the absence of pre-tumorous lesions with a more impressive mucosal inflammation, likely due to reduced epithelial proliferation and repair caused by the absence of IL-33 signaling. At sacrifice, increased number and size of polyps were observed in WT versus IL-33KO and ST2KO mice. Conclusions: Our results suggest that activation of the IL-33/ST2 axis sustains tumorigenesis in the murine model of colitis-associated CRC. Further studies are underway to determine mechanisms of action that support these findings.